Education and Work in the Time of Flexibility. Reconsider the Pedagogical Potential in the Existentialist Planning - Sciannamea, Roberta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays European Unionsupport many training projects reserved to “young adults”, that should sustainthe creation of skills and competences that will enable them to move in the business world. The liquid-times scenario is leading young adults to the loss of the capacity of thinking about long-term project. Using the Educational Clinic approach –whichlegitimate the opportunity of a crossed and inter-disciplinary reading of the educational fact – we try to reason on the conditions that made the pedagogical setting an alcove for the existential planning of the individual, transcending the simple transferred knowledge.The purpose is to go back and ask ourselves about the contemporary context with a look that is enriched by the experienced elements, in order to show a possible niche of the education device, in which the disclosure of the idea of education as a space of potential development for the existential design can be possible.